GREEN SYNTHESIS AND STRUCTURAL CHARACTERIZATION OF IRON OXIDE NANOPARTICLES FROM ROBINIA PSEUDOACACIA L. FRUITS FOR DYE REMOVAL FROM AQUEOUS SOLUTIONS - DEMIR, Semra; AKAR, Bülent; BALTACI, Cemalettin (Studia Universitatis Babeș-Bolyai Chemia, 2026)
In this study, iron oxide nanoparticles were produced and characterized using a green synthesis method with Robinia pseudoacacia fruits. The structural and functional properties of the nanoparticles were investigated using XRD, TEM/EDX, and FTIR analyses. The results indicated that the produced iron oxide nanoparticles had nanoscale particle sizes and exhibited a poorly crystalline (predominantly amorphous) structure according to XRD analysis. The comparative adsorption performance of the synthesized FeONPs and fruit powder in the removal of malachite green (MG), phenol red (PR) and methylene blue (MB) from aqueous solutions was evaluated. According to the results, the adsorption capacity followed the order MB> MG > PR. FeONPs exhibited consistently higher Qₑ values across all dye systems compared to the fruit powder. High removal efficiencies were obtained at low and moderate initial concentrations, while increasing the adsorbent dose enhanced the overall removal but resulted in a reduction in the adsorption capacity per unit mass. The obtained findings indicate that biosynthesized iron oxide nanoparticles can be used as an efficient and environmentally friendly adsorbent for eliminating environmental pollutants.